2015
DOI: 10.1002/ejlt.201400136
|View full text |Cite
|
Sign up to set email alerts
|

Olive oils from Campos de Hellin (Spain) exhibit significant varietal differences in fatty acid composition, sterol fraction, and oxidative stability

Abstract: The Spanish region of Campos de Hellin (Albacete) is characterized by a wide range of olive varieties (Arbequina, Benizal, Cornicabra, Cuquillo, Injerta, Manzanilla Local, Manzanilla de Sevilla, Negrilla, Picual), which provides different physicochemical and sensory characteristics to the oils. Thus, the knowledge of these characteristics may help develop more balanced oils. Monovarietal virgin olive oils from the different varieties grown in this area were characterized from the physicochemical and sensory po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Growing season had no significant effect. In other studies, harvest year had a significant effect on the majority of sterols and triterpene diols [13], although significantly interacting with other factors [102,104,105,115,121,151,165]. In a study with seven Spanish varieties grown in five growing regions, in a direct comparison variety had a stronger influence than geographical location on β-sitosterol, ∆ 5 -avenasterol, and total sterols, expressed as a percentage of variance [74].…”
Section: Influence Of Other Factorsmentioning
confidence: 76%
See 2 more Smart Citations
“…Growing season had no significant effect. In other studies, harvest year had a significant effect on the majority of sterols and triterpene diols [13], although significantly interacting with other factors [102,104,105,115,121,151,165]. In a study with seven Spanish varieties grown in five growing regions, in a direct comparison variety had a stronger influence than geographical location on β-sitosterol, ∆ 5 -avenasterol, and total sterols, expressed as a percentage of variance [74].…”
Section: Influence Of Other Factorsmentioning
confidence: 76%
“…In virgin olive oils produced from a number of olive varieties, relative amounts of particular sterols and/or triterpenes diols were found to be higher or lower than the limits prescribed by the current regulation (Table 2). For particular Spanish Cornicabra [98,141] and Benizal monovarietal oil samples [102,105], a campesterol content higher than 4.0% was found in several studies, suggesting it as a possible varietal peculiarity. A similar case was found in particular samples of Greek Koroneiki [118] and Turkish Memecik [121], and in a whole series of oils from minor varieties in various Mediterranean countries (Table 2).…”
Section: Influence Of Varietymentioning
confidence: 97%
See 1 more Smart Citation
“…The oils made from the Martin Galgo variety showed lower values, which does not mean it constitutes a fraud oil, as it seems to be an intrinsic characteristic of this variety. The only variety with average values for this parameter was Arbequina, although much lower than those found in nearby olive regions [28,38,63]. In the analysis of the triterpenic dialcohols (erythrodiol + uvaol), the Martin Galgo variety stood out again, with very low values, although without significant differences from the Arbequina and Manzanilla varieties.…”
Section: Triterpenic Sterol and Dialcohol Compositionmentioning
confidence: 83%
“…The mean values of this parameter were significantly lower in the first season tested due to the higher level of MI presented by the cultivars [13]. The high stability of "Cornicabra" oils is a well-known fact due to their high phenol content [26]. Alvarruiz et al [27] and Montaño et al [28] found that "Cornicabra" oils were more stable than "Arbequina" and "Cacereña" oils, respectively.…”
Section: Oil Analysismentioning
confidence: 90%